Circ_0015382 is associated with preeclampsia and regulates biological behaviors of trophoblast cells through miR-149-5p/TFPI2 axis. (May 2021) - Hu, Zongyan; Dong, Changmin; Dong, Qian
Abstract: Introduction: Circ_0015382 expression was found to be up-regulated in preeclampsia (PE) placenta tissues, while the role and molecular mechanisms of circ_0015382 in PE remain unclear. Methods: The expression of circ_0015382, microRNA (miR)-149-5p, and tissue factor pathway inhibitor 2 (TFPI2) was measured using quantitative real-time polymerase chain reaction and Western blot. Cell proliferation, migration, invasion, apoptosis, and cell cycle, were detected using cell counting kit-8, transwell, and flow cytometry assays, respectively. The direct interaction between miR-149-5p and circ_0015382 or TFPI2 was analyzed using the dual-luciferase reporter assay. Results: Circ_0015382 was highly expressed in placental tissues of PE. Overexpression of circ_0015382 suppressed trophoblast cell proliferation, migration, invasion and epithelial-mesenchymal transition (EMT), but induced apoptosis and cell cycle progression, while circ_0015382 knockdown showed inverse effects. MiR-149-5p was confirmed to be a target of circ_0015382, and silencing miR-149-5p reversed the regulatory effects of circ_0015382 knockdown on trophoblast cell biological behaviors. MiR-149-5P was expressed at lower levels in placental tissues of PE, while the expression of its target TFPI2 was higher. Importantly, circ_0015382 could regulate TFPI2 expression via miR-149-5p. Additionally, miR-149-5p was shown to promote trophoblast cell growth, migration, invasion and EMT through TFPI2. Discussion: Circ_0015382 was associated with the onset and development of PE through suppressing trophoblast cell growth, migration, invasion and EMT via miR-149-5p/TFPI2 axis, revealing a new insight into the pathogenesis of PE and a potential therapeutic target for PE treatment. Highlights: Circ_0015382 was highly expressed and miR-149-5p was lowly expressed in placental tissues of PE. Circ_0015382 knockdown or miR-149-5p re-expression promoted trophoblast cell growth, migration, invasion and EMT. MiR-149-5p directly interacted with circ_0015382 or TFPI2. Silencing miR-149-5p attenuated the regulatory effects of circ_0015382 knockdown on trophoblast cell biological behaviors. MiR-149-5p promoted trophoblast cell growth, migration, invasion and EMT through TFPI2.